Application of VAM to examine the virtual tourism adoption among undergraduate students in Malaysia / Khaslinda Akasyah Mujin and Tay Kai Xin - Mujin, Khaslinda Akasyah; Tay, Kai Xin (2023)
Over the past few years, there has been a gradual yet consistent surge in the utilization of virtual tourism (VT) within the tourism industry despite the challenges posed by the recent COVID-19 outbreak. Similarly, there is a prevailing belief that VT in the educational sector holds considerable value and offers substantial benefits in shaping an innovative educational experience. However, VT is still seen as a new thing in Malaysia's education sector. Thus, this research aims to examine the undergraduate students' VT adoption by using Value-based Adoption Model (VAM). Employing a quantitative method, 306 completed questionnaires were analyzed using Stata (version 14.2) and Structural Equation Modelling (SEM). The empirical results revealed that the perceived usefulness and enjoyment were positively affecting the VT behavioural intention. However, the perceived cost was found to be statistically significant and positively affected the behavioural intent of VT. The high cost of using VT shows that sacrifices are required. Therefore, the perceived cost would not be a barrier to students taking up VT. This study was limited to only focusing on examining undergraduate students' VT behavioural intention. To provide a more comprehensive understanding of VT adoption, future research could consider extending the study to include a wider demographic range. Considering the evolving nature of technology and tourism trends, longitudinal studies could be conducted to track changes in VT adoption patterns over time, providing valuable insights into the long-term impact of VT on the tourism industry.